Rural Women in Leadership Positive Factors in Leadership Development - McVay, Lori Ann (CABI, 2014)
Northern Ireland – with its vibrant rural communities and dynamic network of rural women’s groups – supplied a rich localized site for this study. The six Rural Women’s Networks in Northern Ireland – and an umbrella organization, the Northern Ireland Rural Women’s Network (NIRWN) – provided a natural starting point for identifying participants, as their directors and other staff mem- bers ﬁ t well within the proﬁ le of rural women in leadership. And though not all rural women in the region are involved with the Rural Women’s Networks, the networks actively promote the advancement of Northern Ireland’s rural women at local, regional and national levels. This promotion is greatly needed, given the continued presence of gender inequalities and inadequacies in the areas of child- care, transportation, employment opportunities and training (Shortall, 2003; Rural Women’s Networks, Northern Ireland Rural Women’s Network, 2007). The networks, along with Northern Ireland’s Department of Agriculture and Rural Development (DARD), have called for leadership development in rural areas as a crucial means of addressing these and other pressing issues. This study was therefore undertaken as a means of ascertaining the key factors facilitating the development and acquisition of leadership skills among women leaders from rural areas of Northern Ireland. Two secondary questions guided the research design. First, what people, organizations and/or events supported these women’s development and acquisition of leadership skills? And, secondly, what thought processes and choices did they exercise in order to overcome obstacles in their development as leaders? As a matter of situating the study within current aca- demic dialogue, research began with a review of pertinent literature.